ISLAM AND INFORMATION PERSPECTIVE ON SOME MODERN COMMUNICATION TECHNOLOGIES BETWEEN LEGALITY AND PROHIBITION (International Seminar on Syariah and Law (INSLA), 2020)
Islam as a religion condemned in equivocal terms, forms of innovation in the religion, as related from prophetic traditions: “whoever introduces something new (Bid’ah) into this affair of ours (Religion of Islam), something which does not originally belongs to it, it is rejected”. Life in the modern time (21stcentury) is full of worldly innovations, some of which are even utilized in furtherance of Islamic activities, ethics and values. This paper aimed at an attempt to explore on the status of such innovative objects as well as their position in Islamic Shari’ah. It is in the light of the above that the research chooses and focused on Information and Communication Technologies (ICT’s)and its related innovations and termedas“ Islam and Information perspectives on some Modern Communication Technologies (ICT’s); between Legality and Prohibition” This is because some Muslims misunderstood the real Islamic rules, to the extent that some denominations tagged the western education and technological innovations as forbidden. The discrepancy between the plight of Islam and different innovations that have been attached to it can be mainly found through the interplay and the features of different technological advancements such as social networks, computer applications, computer usage, cyber related crimes & social menace (such as hacking, fraud on the net, computer virus, computer games, pornography and some related issues)were observed).Documents analysis were employed for the data collection in conducting this work study. The findings show that the (ICT’s) application in Islamic perspective is very valuable to procure the possible solutions to the predicaments faced by the entire humanity in all life ramifications be it socio-economic, legal and political advancements and the host of others.